Sarcosine Is Uniquely Modulated by Aging and Dietary Restriction in Rodents and Humans - Ryan O. Walters; Esperanza Arias; Antonio Diaz; Emmanuel S. Burgos; Fangxia Guan; Simoni Tiano; Kai Mao; Cara L. Green; Yungping Qiu; Hardik Shah; Donghai Wang; Adam D. Hudgins; et al. (Cell Reports, 2018)
Summary: A hallmark of aging is a decline in metabolic homeostasis, which is attenuated by dietary restriction (DR). However, the interaction of aging and DR with the metabolome is not well understood. We report that DR is a stronger modulator of the rat metabolome than age in plasma and tissues. A comparative metabolomic screen in rodents and humans identified circulating sarcosine as being similarly reduced with aging and increased by DR, while sarcosine is also elevated in long-lived Ames dwarf mice. Pathway analysis in aged sarcosine-replete rats identify this biogenic amine as an integral node in the metabolome network. Finally, we show that sarcosine can activate autophagy in cultured cells and enhances autophagic flux in vivo, suggesting a potential role in autophagy induction by DR. Thus, these data identify circulating sarcosine as a biomarker of aging and DR in mammalians and may contribute to age-related alterations in the metabolome and in proteostasis. : In a comparative metabolic screen of rodents and humans, Walters et al. show that circulating sarcosine is similarly reduced with aging and increased by dietary restriction. They demonstrate that sarcosine activates macroautophagy in cultured cells and in vivo, suggesting a role in improved proteostasis via dietary restriction. Keywords: sarcosine, aging, metabolomics, dietary restriction, autophagy, GNMT, glycerophospholipids, amino acids, glycine, methionine